2005
DOI: 10.1001/archinte.165.10.1095
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Overview of Warfarin and Its Drug and Food Interactions

Abstract: The number of drugs reported to interact with warfarin continues to expand. While most reports are of poor quality and present potentially misleading conclusions, the consistency of reports of interactions with azole antibiotics, macrolides, quinolones, nonsteroidal anti-inflammatory drugs, including selective cyclooxygenase-2 inhibitors, selective serotonin reuptake inhibitors, omeprazole, lipid-lowering agents, amiodarone, and fluorouracil, suggests that coadministration with warfarin should be avoided or cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
695
2
44

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,004 publications
(765 citation statements)
references
References 219 publications
9
695
2
44
Order By: Relevance
“…However, several patient dependent factors have been demonstrated to have impact upon warfarin's bioavailablity, for example diet, genetic disposition, age, pharmaceutical regime (Holbrook et al, 2005). An issue intimately related to the complexity of warfarin's bioavailability is its chameleon-like behaviour, whereby the relative concentrations of the ensemble of warfarin isomers present can be profoundly influenced by molecular environment (Karlsson et al, 2007(Karlsson et al, , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…However, several patient dependent factors have been demonstrated to have impact upon warfarin's bioavailablity, for example diet, genetic disposition, age, pharmaceutical regime (Holbrook et al, 2005). An issue intimately related to the complexity of warfarin's bioavailability is its chameleon-like behaviour, whereby the relative concentrations of the ensemble of warfarin isomers present can be profoundly influenced by molecular environment (Karlsson et al, 2007(Karlsson et al, , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the best described example of this phenomenon is testing for genetic variance in CYP2C9 and VKORC1 which have been shown to alter patients' response to Coumadin, a medication that is used by millions of people in the United States and is associated with a significant risk of bleeding. 9 An initial report by AEI-Brooking Joint Centre for Regulatory Studies suggested that testing for polymorphisms in these genes would decrease health care spending in the United States by up to two billion dollars annually. 10 This report, which was published before any clinical study had empirically demonstrated improved patient outcomes, has been subsequently followed by several studies that are more discouraging.…”
Section: Diagnostic and Drug Researchmentioning
confidence: 99%
“…Its metabolism can be increased or decreased by numerous medications, foods, and alcohol, but the evidence to support the clinical consequences of these interactions is limited. 9 Warfarin co-administration with azole antibiotics, macrolides, quinolones, non-steroidal anti-inflammatory drugs, serotonin uptake inhibitors, lipid lowering agents, amiodarone, and fluoruracil should be done only with close monitoring. 9,10 From 0.4 to 2.0% of patients require transfusion, hospitalization, or surgery due to bleeding caused by warfarin toxicity.…”
Section: Risks and Side Effectsmentioning
confidence: 99%
“…9 Warfarin co-administration with azole antibiotics, macrolides, quinolones, non-steroidal anti-inflammatory drugs, serotonin uptake inhibitors, lipid lowering agents, amiodarone, and fluoruracil should be done only with close monitoring. 9,10 From 0.4 to 2.0% of patients require transfusion, hospitalization, or surgery due to bleeding caused by warfarin toxicity. This outcome is given as one of the most common reasons sited for the underutilization of warfarin anticoagulation.…”
Section: Risks and Side Effectsmentioning
confidence: 99%